2019
DOI: 10.1016/j.icarus.2019.05.027
|View full text |Cite
|
Sign up to set email alerts
|

GRAIL-identified gravity anomalies in Oceanus Procellarum: Insight into subsurface impact and magmatic structures on the Moon

Abstract: anomalies are analyzed on the Moon's nearside. 20 • The amplitudes of the anomalies require a deep density contrast. • One 190-km anomaly with crater-related topography is suggestive of mantle uplift. • Marius Hills anomalies are consistent with intruded dike swarms. • An anomaly south of Aristarchus has a crater rim and possibly magmatic intrusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 66 publications
3
41
0
Order By: Relevance
“…Our 3D inversion results reveal a bowl‐shaped anomaly in the vertical (Figure ) and a QCMA in map view (Figures ). These results are consistent with previous studies on the QCMAs (e.g., Deutsch et al, ; Evans et al, ), and HG3 appears as a circular feature formed by an impact event. The feature does not, however, show a prominent surface basin structure (Figure ), due to burial of basalts (Qian et al, ) that is common to small impact craters (Melosh et al, ; Miljković et al, ; Neumann et al, ) and QCMAs (Evans et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our 3D inversion results reveal a bowl‐shaped anomaly in the vertical (Figure ) and a QCMA in map view (Figures ). These results are consistent with previous studies on the QCMAs (e.g., Deutsch et al, ; Evans et al, ), and HG3 appears as a circular feature formed by an impact event. The feature does not, however, show a prominent surface basin structure (Figure ), due to burial of basalts (Qian et al, ) that is common to small impact craters (Melosh et al, ; Miljković et al, ; Neumann et al, ) and QCMAs (Evans et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…One possibility is that the volcanic activity in the western Rümker region is fed through dike‐like features, which are connected to a magma chamber located entirely in the mantle and cannot be resolved with the resolution (~4.5 km) of our data. This is also supported by Deutsch et al () who suggested that most of the volcanic activities in Oceanus Procellarum were fed through dikes.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations